PENGARUH PERTUMBUHAN PENJUALAN DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL (JEB17 : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of sales growth and asset structure on capital structure. This study was conducted on manufacturing sub-sector companies in the LQ45 category listed on the Indonesia Stock Exchange for the 2018-2022 period. The population used was all manufacturing sub-sector companies in the LQ45 category listed on the Indonesia Stock Exchange for the 2018-2022 period. The number of samples used in this study was 9 companies with a purposive sampling method. The data collection technique used company annual report documentation and the collected data was analyzed using IBM SPSS Version 25 analysis. The results of the study showed that simultaneously the variables of sales growth and asset structure simultaneously had a significant effect on capital structure. While partially the sales growth variable did not have a significant effect on capital structure. The asset structure variable had a significant effect on capital structure. Keywords: Sales Growth, Asset Structure, and Capital Structure.